Remission and Low Disease Activity Status (LDAS) protect lupus patients from damage occurrence: data from a multiethnic, multinational Latin American Lupus Cohort (GLADEL). Issue 12 (22nd September 2017) - Ugarte-Gil, Manuel Francisco; Wojdyla, Daniel; Pons-Estel, Guillermo J; Catoggio, Luis J; Drenkard, Cristina; Sarano, Judith; Berbotto, Guillermo A; Borba, Eduardo F; Sato, Emilia Inoue; Tavares Brenol, João C; Uribe, Oscar; Ramirez Gómez, Luis A; et al.
Abstract : Objective: To evaluate disease activity statuses' (DAS') impact on systemic lupus erythematosus (SLE) outcomes. Materials and methods: Four DAS were defined: remission off-therapy: SLE Disease Activity Index (SLEDAI)=0, no prednisone or immunosuppressive drugs (IS); remission on-therapy: SLEDAI=0, prednisone ≤5 mg/day and/or IS (maintenance); low (L) DAS: SLEDAI ≤4, prednisone ≤7.5 mg/day and/or IS (maintenance); non-optimally controlled: SLEDAI >4 and/or prednisone >7.5 mg/day and/or IS (induction). Antimalarials were allowed in all. Predefined outcomes were mortality, new damage (increase of at least one Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) damage index (SDI) point) and severe new damage (increase of at least 3 SDI points). Univariable and multivariable Cox regression models were performed to define the impact of DAS, as time-dependent variable, on these outcomes. Results: 1350 patients were included, 79 died during follow-up, 606 presented new and 177 severe new damage. In multivariable analyses, remission (on/off-therapy) was associated with a lower risk of new (HR 0.60; 95% CI 0.43 to 0.85), and of severe new damage (HR 0.32; 95% CI 0.15 to 0.68); low disease activity status (LDAS) was associated with a lower risk of new damage (HR 0.66; 95% CI 0.48 to 0.93) compared with non-optimally controlled. No significant effect on mortality was observed. Conclusions: Remission was associated with a lower risk of new and severe new damage; LDAS with a lower risk of new damage after adjusting for other damage confounders.